MOBILE CONTROLLED FLOOR CLEANING ROBOT BY USING RASPBERRY PI - Sunil Lendave , Nitin Gujare,Rushikesh More,Aditya Pawar,S.A.Inamdar (International Journal of Innovations in Engineering Research and Technology, 2022)
Robots have proven to be an important part of daily life because they can effectively help humans perform various application. In this article, we are considering one of the applications of the clean form. With this in mind, we propose a Arduino control model to perform the required cleaning operations. The main purpose of the project is to develop a low-maintenance, A cost-effective multifunctional prototype robot that can perform dry cleaning and wet cleaning. It can operate in autonomous mode and is designed to It has some additional functions, such as ultraviolet sterilization and vacuum cleaner. All these features help to improve people’s lifestyle Humanity.